Promenade Abroad with Bruno Schulz - Banks, Brian R (Załącznik Kulturoznawczy, 2023)
The article depicts ethnic, religious, as well as cultural and literary background of Bruno Schulz and his work. The author argues with some Schulz’s biographers and commentators in order to differentiate between facts and ‘myths’ or interpretations of writer’s life. Moreover, the author traces the main lines of Schulz’s foreign reception and addresses some critical remarks about translations of his work into English, as well as about the other examples of reading and popularizing Schulz’s legacy and heritage, especially in Anglophone cultural contexts.